Micronutrient Foliar Spray on Growth Performance of Green Gram (Vigna radiata L.) - Nayak, Smitanjali; Nayak, Debabrata; Parida, Sagarika (Asian Journal of Biological and Life Sciences, 2020)
Fertilizer application is an important source to increase the production in agricultural practices. Among various cultural practices, foliar nutrition is one of the important methods as the spray of micronutrients and fertilizers facilitate easy and quick utilization of nutrients. In this study the plant growth attributes like height, number of root nodules and the chlorophyll content was observed by foliar spraying of 1% Foliar feed spray, 1% Humic acid liquid fertilizer, 2% NPK (20:20:20) and 2% MAP (12:61:00) in three replicate pots containing soil as control and in variable concentration of soil and compost in 2:1, 2:2, 3:1 and 4:1 ratio. The highest plant growth was recorded in spraying of foliar feed spray and MAP (12:61:00). Humic liquid fertilizer and NPK (20:20:20) in control conditions was found to be effective. Highest nodulation was recorded in plants treated with the foliar feed spray and MAP (12:61:00) in different soil and compost ratios. Like that in case of chlorophyll estimation it has been observed that the highest chlorophyll a (0.13 mg/g) content was found in the plants grown in foliar application of NPK fertilizers applied in soil and compost (3:1 ratio) and the highest chlorophyll b (0.22 mg/g) was recorded in the plants grown both in NPK fertilizers and humic acid fertilizer foliar application and the highest carotenoid content (1.608 mg/g) was estimated in foliar application of humic liquid fertilizer in control pots.
Keywords: Chlorophyll content; Fertilizer; Foliar spray; Micronutrients; Root nodules